ACADEMIC IBRAHIM MOMINOV: MY FIRST TEACHER IS MY MOTHER - Ibodova , Nasiba (Educational Research in Universal Sciences, 2024)
this article reflects on the memories of the academician Ibrahim Mominov, who laid the foundation stone of the Uzbek school of philosophy, and his parents, the venerable Sister Magfirat. Also, the scientist’s research on the development of science was analyzed.